Fascism in contemporary Brazil and the counterinsurgency state - Santos, José Whellison Brito dos (Argumentum, 2021)
Fascism, as a manifestation of reality, has emerged once again in Brazil and the western world, this article is a contribution to the debate surrounding it. Bibliographic research addresses how analyses carried out by Ruy Mauro Marini on the fascist tendencies of the 1964 Coup can provide interpretative keys to the present. This exposition in five parts, founded on the categories 0f Fascism and the Counterinsurgency State, raises questions around the participation of the monopolistic bourgeoisie in the construction of coups d’état, its fascist tones, the role of the military, the category of fascism as expressed by other Brazilian Marxist thinkers and ends with some notes and questions about fascism in contemporary Brazil.